African Union Great Green Wall Initiative Strategy and Ten-Year Implementation Framework: Ecosystem Restoration and Livelihoods Resilience (2024-2034) - African, Union (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This brief outlines the proposed coordination and implementation approach of the new African Union Great Green Wall Initiative (GGWI) Strategy and Ten-Year Implementation Framework (2024–2034). It presents the structure and roles of GGWI bodies and supporting institutions across all levels, from international to community scale, and emphasizes the importance of private sector engagement throughout. The brief details the proposed coordination arrangements, including indicative relationships among key institutions and stakeholders. It also sets out proposed membership criteria for countries, international and national organizations, subnational bodies, networks, and private sector actors. Finally, it describes the proposed criteria for endorsement and the inclusion of new initiatives contributing to the GGWI’s objectives.